Ao Cha (Blue Shot) / Aishah Syaza Kamarudin ... [et al.] - Kamarudin, Aishah Syaza; Mohamad Isa, Farrisa Izzati; Rachel Linus, Raynie; Saifulbahri, Siti Suliana
Our country is still fighting Covid-19, and this episode has changed people's lives, particularly in terms of physical activity, time, and mental health. As a result of studying the current situation in the country, Ao Cha's Company came up with the idea of creating a tea known as a Blue shot with a new speciality in terms of aroma and taste, and Ao Cha also uses natural ingredients in their product. Not only that, Ao Cha improved their tea by using the freeze-dried method, which results in a cube shape that makes it easier for the Blue Shot to dissolve in water with less wasted time. Blue shot tea is a nutritious instant beverage with a 'easy dissolve texture and delightfully sweet juicy flavour.' Ao Cha Company intends to assist people in reducing health issues by producing a tea with a new appearance and an affordable price. To ensure the success of this project, Ao Cha Company decides to support a local business by purchasing fresh ingredients from them. Ao Cha Company has also decided to sell their product in supermarkets and clinics. In addition, Ao Cha will require a lab or machine to manufacture the product. As a result, Ao Cha will hire expert employees and continue to excel in their packaging. Ao Cha's target market for this product will be students, workers, parents, and senior citizens. Because the majority of them has the chances on facing health issues especially during the Covid-19 pandemic. Finally, Ao Cha Company hopes that investors will assist in the production of this product for our goods. This Blue's shot will be a good product to consume, as well as a good opportunity for our country to have friend- business relations with other countries.